Teaching competence in future Computer Science teachers in Ecuador - Rojas-Viteri, Juan Carlos (2023)
The knowledge society and economy of the 21st century demand that students develop the necessary skills and abilities to face the requirements of adult life. Thus, future teachers of computer science secondary education in Ecuador, due to their technical-pedagogical training, face the challenge of developing the digital teaching competence to help their students to face the technological challenges that the current world demands. The present study aimed to diagnose and analyze the level of mastery in the 5 areas of digital competence in the students of the Pedagogy of Experimental Sciences of Computer Science at the Central University of Ecuador, through the application of a questionnaire created by professors Débora Martín Rodríguez, María Saénz, Raúl Santiago and Edurne Chocarro, professors of two renowned universities in Spain. In addition, the instrument was validated by local experts. To measure the reliability of the questionnaire, Cronbach's alpha coefficient was used for each dimension of digital competence in teaching, obtaining a score of over 0.90. The methodology used was empirical-analytical and descriptive, using a non-probabilistic sampling, at the convenience of the researchers, of 161 students of different levels and subjects. Among the main conclusions found were that the least developed areas of teaching digital competence are problem solving and safety.